2010
DOI: 10.2337/dc09-1711
|View full text |Cite
|
Sign up to set email alerts
|

Collaborative Care Management of Major Depression Among Low-Income, Predominantly Hispanic Subjects With Diabetes

Abstract: OBJECTIVETo determine whether evidence-based socioculturally adapted collaborative depression care improves receipt of depression care and depression and diabetes outcomes in low-income Hispanic subjects.RESEARCH DESIGN AND METHODSThis was a randomized controlled trial of 387 diabetic patients (96.5% Hispanic) with clinically significant depression recruited from two public safety-net clinics from August 2005 to July 2007 and followed over 18 months. Intervention (INT group) included problem-solving therapy an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
235
1
2

Year Published

2012
2012
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 202 publications
(243 citation statements)
references
References 25 publications
5
235
1
2
Order By: Relevance
“…Previous trials in the research field of diabetes and depression to a large extent included primary care patients (e.g., [12,13]) and the rare positive effects on glycemic control were mainly seen in studies conducted in primary care patients (13,38,39). In contrast, we recruited participants exclusively from secondary care study sites.…”
Section: Selection Of Patientsmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous trials in the research field of diabetes and depression to a large extent included primary care patients (e.g., [12,13]) and the rare positive effects on glycemic control were mainly seen in studies conducted in primary care patients (13,38,39). In contrast, we recruited participants exclusively from secondary care study sites.…”
Section: Selection Of Patientsmentioning
confidence: 99%
“…These included the measurement of depression with SCID and HAMD interviews by trained clinical psychologists (instead of questionnaires, as in some important trials on this topic [12,13]), the video-controlled monitoring of adherence of psychologists to the CBT manual, the establishment of an independent scientific advisory board, the data management, and data validation with intense validation strategies. Finally, we limited bias due to center or investigator effects by including eight clinical psychologists and 70 trial sites across Germany.…”
Section: Study Limitations and Strengthsmentioning
confidence: 99%
See 1 more Smart Citation
“…[82][83][84][85][86][87] These models involve routine depression screening among individuals with uncontrolled diabetes, on-site care managers providing between-visit phone calls to assess diabetes self-care adherence, and on-site behavioral health providing brief interventions and SMG during the clinic visit. CCMs of diabetes and depression yield improvements in depression-related outcomes, [87][88][89][90][91] increased adherence to diabetes and depression self-management, 92,93 and decreased rates of mortality, compared to usual care. 94 Limited quantitative data are available supporting the association of collaborative care with improvement in HbA1c; however, one study showed that the incorporation of health coaching into diabetes management was associated with accelerated HbA1c reduction and improved mood as measured by Hospital Anxiety and Depression Scale (HADS).…”
Section: -73mentioning
confidence: 99%
“…This study identifies many of the same barriers found in the literature that categorize Latino clinical trial retention barriers: familial relationships and issues [22], lack of transportation, employment interferences [23], economic stress [24] and financial costs [25], insufficient caregiving resources to meet demands [26], practical barriers [24,27], like interference with other top priorities of life such as work and family obligations [26], and systems barriers [28][29][30]. Andersen and Newman's [16] framework helps illuminate new and important Predisposing "Psychological Coping" Belief barriers specific to this co-morbid population, that are not specifically indicated in the literature (i.e., "feeling better;" "not interested;" "emotional stress;" grief over "loss;" untreated panic attacks; and anxiety over fertility issues).…”
Section: Discussionmentioning
confidence: 99%